We have to factor a^4 - b^16

we use x^2 - y^2 = (x +y)(x - y)

a^4 - b^16

=> (a^2 - b^8)(a^2 + b^8)

=> (a - b^4)(a + b^4)(a^2 + b^8)

**Therefore a^4 - b^16 = (a - b^4)(a + b^4)(a^2 + b^8)**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now